UV irradiation-induced production of monoglycosylated biglycan through downregulation of xylosyltransferase 1 in cultured human dermal fibroblasts. Issue 1 (July 2015) - Jin, Cheng Long; Oh, Jang-Hee; Han, Mira; Shin, Min Kyeong; Yao, Cheng; Park, Chi-Hyun; Jin, Zhe Hu; Chung, Jin Ho
Highlights: UV increases monoglycosylated biglycan production in cultured fibroblasts. UV decreases XYLT1 mRNA expression much more than XYLT2. Only XYLT1 donwregulation induces monoglycosylated biglycan production. XYTL2 seems to react with only serine 42 but not with serine 47 on the biglycan core protein. Abstract: Background: Biglycan (BGN) is a proteoglycan composed of a 42-kDa core protein and two glycosaminoglycan (GAG) chains, and known to be involved in structural, space-filling functions and many physiological regulations in the skin. Objective: To investigate ultraviolet (UV) irradiation-induced changes of BGN protein and its GAG chain synthesis in cultured human dermal fibroblasts. Methods: UV irradiation-induced or xylosyltransferase (XYLT) 1 siRNA-mediated smaller-sized protein bands detected by Western blot using BGN antibodies were identified as monoglycosylated forms of BGN, using BGN siRNA-mediated knockdown and chondroitinase ABC (ChABC). Differential activity of XYLT1 and 2 on BGN core protein was investigated by size shift of S42A- and S47A-BGN mutants to core protein size caused by XYLT1 siRNA transfection or UV irradiation. Results: After UV irradiation, intact form of BGN protein (I-BGN) and core protein form were reduced in cultured fibroblasts, but other smaller-sized bands were observed to be increased. These smaller-sized ones were reduced by transfection of BGN siRNA, and shifted to the core protein size by treatment with ChABC, suggesting that they are defectively-glycosylated forms of BGN (D-BGN) protein. UV irradiation also decreased mRNA expression levels of XYLT1 and 2, which are responsible for initiation of GAG chain synthesis. UV-mediated reduction of XYLT1 expression was much stronger than that of XYLT2. Furthermore, siRNA-mediated down-regulation of XYLT1 resulted in the increase of D-BGN and the decrease of I-BGN, while down-regulation of XYLT2 resulted in no change of D-BGN and I-BGN, suggesting that the XYLT1 may react with both GAG-attaching serine sites of BGN; however, XYLT2 may prefer to react one of them. Another dermatan sulfate (DS) proteoglycan, decorin, showed no or a little change of its molecular weight by UV irradiation or XYLT1 siRNA transfection, suggesting that DS synthesis may not be a critical factor in formation of D-BGN. Co-transfection with XYLT1, 2 siRNAs and wild-type or mutant forms of BGN overexpression vectors revealed that S42A-BGN showed size reduction to core protein size by XYLT1 downregulation, but S47A-BGN did not, suggesting that XYLT2 can react only with S42 on BGN core protein. With UV irradiation, both S42A-BGN and S47A-BGN showed size reduction, which is probably because UV-caused downregulation of both XYLTs and overexpression condition resulted in incomplete glycosylation and secretion. Conclusions: UV irradiation-induced increase of BGN monoglycosylated forms in cultured human dermal fibroblasts is resulted from dominance of XYLT2 activity, which acts only at S42 on BGN core protein, caused by UV-mediated stronger reduction of XYLT1.